Asymmetric Synthesis of Tetrahydropyridines via a Brønsted Acid Catalyzed Aza-Diels–Alder Reaction - Beceño, Christian; Krappitz, Tim; Raabe, Gerhard; Enders, Dieter (Synthesis, 2015)
The asymmetric synthesis of tetrahydropyridines employing a normal electron-demanding aza-Diels–Alder reaction has been developed. The [4+2] cycloaddition of ethyl glyoxylate imine with aryl-substituted 2-silyloxy-1,3-butadienes is catalyzed by 5 mol% of a BINOL-derived phosphoric acid and in general leads to good yields and ee values with good to excellent diastereoselectivities. The cycloadducts can be further converted into the corresponding piperidinones, which are important pipecolic acid derivatives.
Keywords: aza-Diels–Alder reaction; asymmetric synthesis; Brønsted acid; organocatalysis; glyoxylate imine